Moderate Exercise in Spontaneously Hypertensive Rats Is Unable to Activate the Expression of Genes Linked to Mitochondrial Dynamics and Biogenesis in Cardiomyocytes - Quiroga, Clara; Mancilla, Georthan; Oyarzun, Ingrid; Tapia, Anita; Caballero, Mia; Gabrielli, Luigi A.; Valladares-Ide, Denisse; del Campo, Andrea; Castro, Pablo F.; Verdejo, Hugo E. (Frontiers in Endocrinology, 2020)
Hypertension (HTN) is a major preventable cause of cardiovascular disease. Regular aerobic exercise exhibits blood pressure protective effects, improves myocardial function, and may reverse pathologic cardiac hypertrophy. These beneficial effects depend at least partially on improved mitochondrial function; however, the effect of moderate exercise on HTN subjects at a cellular level remain largely unknown. This study aims to investigate the effect of exercise training in the adult spontaneously hypertensive rats (SHRs), focusing on the mitochondrial response to exercise in the myocardium. Methods: Eight-month-old SHRs and their normotensive control - Wistar-Kyoto rats (WKYR) - were randomly assigned to moderate exercise on a treadmill five times per week at 70-85% of the maximum O2 consumption for a total of 8 weeks. A control group of untrained animals was maintained in their cages during the same period. Results: At baseline, SHR presented myocardial remodeling evidenced by left ventricular hypertrophy (interventricular septum 2.08 ± 0.07 vs. 1.62 ± 0.08 mm, p <0.001), enlarged left atria (0.62 ± 0.1 mm vs. 0.52 ± 0.1, p = 0.04) and impaired diastolic function (E/A ratio 2.43 ± 0.1 vs. 1.56 ± 0.2) when compared to WKYR. Moderate exercise did not induce changes in ventricular remodeling but improved diastolic filling (E/A ratio 2.43 ± 0.1 in untrained SHR vs. 1.89 ± 0.16 trained SHR, p < 0.01). Histological analysis revealed increased myocyte transversal section area and collagen fiber accumulation in untrained SHR. While the exercise protocol did not modify the cardiac size, there was a significant reduction of cardiomyocyte area in the SHR-exercise group. Heart titin expression increased only WYKR-exercise animals but remained unchanged in SHR-exercise. Mitochondrial response to exercise also diverged between SHR and WYKR: moderate exercise showed an apparent increase of mRNA levels of Ppargc1α, Opa1, Mfn2, Mff, and Drp1 in WYKR, but remained unchanged in trained SHR rats, which also exhibited increased OPA1 processing. In summary, exercise improves diastolic parameters in SHR rats but fails to activate the cardiomyocyte mitochondrial adaptive response observed in healthy individuals.